Mucosal Immunization with Recombinant Adenovirus Encoding Soluble Globular Head of Hemagglutinin Protects Mice Against Lethal Influenza Virus Infection - Kim, Joo Young (The Korean Association of Immunologists, 2013)
Influenza virus is one of the major sources of respiratory tract infection. Due to antigenic drift in surface glycoproteins the virus causes annual epidemics with severe morbidity and mortality. Although hemagglutinin (HA) is one of the highly variable surface glycoproteins of the influenza virus, it remains the most attractive target for vaccine development against seasonal influenza infection because antibodies generated against HA provide virus neutralization and subsequent protection against the virus infection. Combination of recombinant adenovirus (rAd) vector-based vaccine and mucosal administration is a promising regimen for safe and effective vaccination against influenza. In this study, we constructed rAd encoding the globular head region of HA from A/Puerto Rico/8/34 virus as vaccine candidate. The rAd vaccine was engineered to express high level of the protein in secreted form. Intranasal or sublingual immunization of mice with the rAd-based vaccine candidates induced significant levels of sustained HA-specific mucosal IgA and IgG. When challenged with lethal dose of homologous virus, the vaccinated mice were completely protected from the infection. The results demonstrate that intranasal or sublingual vaccination with HA-encoding rAd elicits protective immunity against infection with homologous influenza virus. This finding underlines the potential of our recombinant adenovirus-based influenza vaccine candidate for both efficacy and rapid production.